Uji Lapang Mesin Parut Sagu Tipe Silinder Variant-02 di Distrik Momi Waren Kabupaten Manokwari Selatan - darma darma darma (Agritechnology, 2023)
Field testing is aimed to test the performance of a machine in the real conditions rather than in laboratory. It is a stage which must be conducted before a machine prototype is produced in large quantities. The objective of this research was field test of cylinder type sago rasping machine variant-01 in Momi Waren Distric, the Regency of Manokwari Selatan. During field test, the machine was operated by sago farmer which was trained previously. The performance of the machine in the field condition was evaluated in term of parameters (a) rasping capacity, (b) starch rendement, (c) starch losses in sago pith waste and (d) fuel consupmtion. Results showed that sago farmers were able to operate the machine easily. During testing, the machine was work properly and there was no technical constrains. In the field condition, the performance of the machine were; (a) rasping capacity 650.44 kg/hour, (b) starch rendement 25.47%, (c) starch losses in sago pith waste 11.33% and (d) fuel consumption 1.5 litre/hour.